A Critique of Exaggerated Libertinism in Thomas Shadwell’s The Libertine - Şafak Horzum (Ideas: Journal of English Literary Studies)
This article argues that The Libertine by Thomas Shadwell, one of the earliest examples of the Restoration comedies, has one of the pioneering roles in portraying the philosophy of the time’s courtiers, libertinism. It is obviously seen in Shadwell’s play that the characteristics of libertinism are not given entirely truly in this Don Juan adaptation, but rather in an exaggerated and criminalised way. In this light, the paper will first discuss the playwright’s socio-political position during the upheaval of the Restoration of Charles II. Secondly, it will set out to explore the play’s position in terms of its exemplary nature in the genre of comedy of manners. Last but not least, libertinism and its characteristics will be analysed through their illustration in the play by means of male characters, particularly Don John, the protagonist.